Protein Kinases Promising Targets for Anticancer Drug Research - Kumar Singh, Rajesh (Biochemistry, 2021)
For the past two decades, the protein kinase family has been an intense area of research for developing anticancer drugs. Despite tremendous advancements in kinase drug expansion, many kinases are still unexplored. As such, this book includes research and review articles from experts that focus on protein kinase signalling pathways as a molecular drug target. Chapters include illustrations and cover such topics as the mechanism of action and anticancer activity of protein kinase inhibitors on various cancer types. They also discuss new opportunities, challenges, and future perspectives in the field.